Cambioxylophagous Pests of Scots Pine: Ecological Physiology of European Populations—A Review - Hlávková, Daniela; Doležal, Petr (Frontiers in Forests and Global Change, 2022)
Climatic extremes have been gathering momentum since the 1880s and are believed to be a long-term factor increasing the mortality of Scots pine trees, Pinus sylvestris (L.) in Europe. Weather monitoring over the past 120 years shows that, in Central Europe, surface air temperatures grow at a rate of 0.18°C per decade. Many changes due to these abiotic stressors are already visible in the forests’ canopy and biodiversity. But the influence of the rise in temperature and in precipitation deficiency brings one more player into this die-back scheme. Bark beetles, and their increasing outbreaks, are further agents acting to accelerate and expand the impacts of weather on trees. While P. sylvestris react to abiotic stressors by decreasing functions of the hydraulic system, mainly the defense system, for bark beetles, warming is a profitable condition. Various bionomy processes are modified: vegetation seasons prolong, larval growth and development rates accelerate, reproductive potential rises, and overwintering success increases. Thus, the insect populations grow, and the infestation pressure on weakened hosts intensifies. Finally, even species of small ecologic importance can cause extensive losses of forest cover. Furthermore, international trade and intercontinental transportation support the potential threat of spreading forest pests far away from their original geographic range. Together with climatic amelioration, pests may adapt to new conditions, establish new prosperous populations, disperse rapidly, and cause prodigious losses. However, detailed information about cambioxylophagous pests on P. sylvestris in Central Europe is still missing. The purpose of our review is to map the bionomy and behavior of six bark beetle species—in particular, the sharp-dentated bark beetle, Ips acuminatus (Gyllenhal, 1827), the six-toothed bark beetle, Ips sexdentatus (Börner, 1767), the common pine shoot beetle, Tomicus piniperda (Linnaeus, 1758), the lesser pine shoot beetle, Tomicus minor (Hartig, 1834), the pine shoot beetle, Tomicus destruens (Wollaston, 1865), the Mediterranean pine engraver, Orthotomicus erosus (Wollaston, 1857) (Coleoptera: Curculionidae: Scolytinae), and the steel-blue jewel beetle, Phaenops cyanea (Fabricius, 1775) (Coleoptera: Buprestidae)—on P. sylvestris in Central Europe, to compare and summarize the available data on European populations, and to try to propose ideas and directions for future research.